Determination of experimental axial and sideways metal flow in open die forging - Aksakal, B.; Osman, F. H.; Bramley, A. N. (Elsevier Sci Ltd, 2008)
For the sake of automation in open die forging; some preliminary experimental calculations such as measurement and calculation of metal flow in lateral and axial directions, and manipulation of the workpiece are evaluated. For a small batch production sequence, first a suitable workpiece manipulator is designed and manufactured accommodating all material displacement and movements, and solutions are presented to calculate the amount of material displaced from under flat tools in the axial and lateral directions. Comparisons between experimental flow measurements and calculations with theoretical results showed good agreement. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: open die forging; metal flow; workpiece manipulation; automation